Induced pluripotent stem cell-derived vascular networks to screen nano–bio interactions. Issue 3 (12th February 2021) - Estronca, Luís; Francisco, Vitor; Pitrez, Patrícia; Honório, Inês; Carvalho, Lara; Vazão, Helena; Blersch, Josephine; Rai, Akhilesh; Nissan, Xavier; Simon, Ulrich; Grãos, Mário; Saúde, Leonor; et al.
Abstract : The vascular bioactivity/safety of nanomaterials is typically evaluated by animal testing, which is of low throughput and does not account for biological differences between animals and humans such as ageing, metabolism and disease profiles. Abstract : The vascular bioactivity/safety of nanomaterials is typically evaluated by animal testing, which is of low throughput and does not account for biological differences between animals and humans such as ageing, metabolism and disease profiles. The development of personalized human in vitro platforms to evaluate the interaction of nanomaterials with the vascular system would be important for both therapeutic and regenerative medicine. A library of 30 nanoparticle (NP) formulations, in use in imaging, antimicrobial and pharmaceutical applications, was evaluated in a reporter zebrafish model of vasculogenesis and then tested in personalized humanized models composed of human-induced pluripotent stem cell (hiPSC)-derived endothelial cells (ECs) with "young" and "aged" phenotypes in 3 vascular network formats: 2D (in polystyrene dish), 3D (in Matrigel) and in a blood vessel on a chip. As a proof of concept, vascular toxicity was used as the main readout. The results show that the toxicity profile of NPs to hiPSC-ECs was dependent on the "age" of the endothelial cells and vascular network format. hiPSC-ECs were less susceptible to the cytotoxicity effect of NPs when cultured in flow than in static conditions, the protective effect being mediated, at least in part, by glycocalyx. Overall, the results presented here highlight the relevance of in vitro hiPSC-derived vascular systems to screen vascular nanomaterial interactions.